DESIGNING TATTO ARTWORK WITH THE CONCEPT OF BALI CULTURE USING THE DARK ART STREAM AT KINK TATTO BALI - Dharma, I Made Agus Wira; Budiarta, I Dewa Putu Gede; Putra, I Gede Jaya (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
This study explores Balinese culture through Dark Art to depict the grandeur and complexity of the community's spirituality. Dark Art, with its dark tones and profound symbolism, reflects the mystical power and sacredness of nature represented by mythological figures like Dewi Durga. In Balinese culture, Dewi Durga symbolizes the formidable forces of nature, revered through various rituals and arts. Her portrayal in a horror-themed style emphasizes not only the terrifying aspects but also the majesty and sacred mystery of nature. Dark Art elements such as horror nuances and Rangda masks enhance the symbolism of the niskala (spiritual) world, a vital aspect of Balinese life. The Rangda mask, often associated with negative forces, represents diseases or spiritual disturbances that are addressed through traditional rituals. The use of these elements illustrates how Balinese people maintain balance between physical and spiritual aspects. The study's artistic outcomes combine Dark Art aesthetics with Balinese traditions, creating a profound visual interpretation of the community's views on nature and spirituality. This approach highlights the significance of the niskala realm in Balinese culture, particularly in preserving harmony in life. The research contributes to understanding how Balinese art and culture utilize Dark Art symbolism to express their beliefs and spiritual practices.